Interprofessional training for final year healthcare students: a mixed methods evaluation of the impact on ward staff and students of a two-week placement and of factors affecting sustainability. Issue 1 (December 2015) - McGettigan, Patricia; McKendree, Jean
Abstract Background Multiple care failings in hospitals have led to calls for increased interprofessional training in medical education to improve multi-disciplinary teamwork. Providing practical interprofessional training has many challenges and remains uncommon in medical schools in the UK. Unlike most previous research, this evaluation of an interprofessional training placement takes a multi-faceted approach focusing not only on the impact on students, but also on clinical staff delivering the training and on outcomes for patients. Methods We used mixed methods to examine the impact of a two-week interprofessional training placement undertaken on a medical rehabilitation ward by three cohorts of final year medical, nursing and therapy students. We determined the effects on staff, ward functioning and participating students. Impact on staff was evaluated using the Questionnaire for Psychological and Social factors at work (QPSNordic) and focus groups. Ward functioning was inferred from standard measures of care including length of stay, complaints, and adverse events. Impact on students was evaluated using the Readiness for Interprofessional Learning Survey (RIPLS) among all students plus a placement survey among medical students. Results Between 2007 and 2010, 362 medical students and 26 nursing and therapy students completed placements working alongside the ward staff to deliver patient care. Staff identified benefits including skills recognition and expertise sharing. Ward functioning was stable. Students showed significant improvements in the RIPLS measures of Teamwork, Professional Identity and Patient-Centred Care. Despite small numbers of students from other professions, medical students' rated the placement highly. Increasing student numbers and budgetary constraints led to the cessation of the placement after three years. Conclusions Interprofessional training placements can be delivered in a clinical setting without detriment to care and with benefits for all participants. While financial support is a necessity, it appears that having students from multiple professions is not critical for a valuable training experience; staff from different professions and students from a single profession can work successfully together. Difficulty in aligning the schedules of different student professions is commonly cited as a barrier to interprofessional training. Our experience challenges this and should encourage provision of authentic interprofessional training experience.